2016
DOI: 10.5897/ijlis2016.0708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of English Language proficiency on students performance in cataloguing and classification courses in polytechnic - based library schools in Nigeria

Abstract: The study investigates the effect of English Language proficiency on student's performance in cataloguing and classification courses in polytechnic-based library schools in Nigeria. This is against the background of the phobia the students have for cataloguing and classification. Descriptive survey method was adopted while a questionnaire, English Language proficiency test and cataloguing and classification test were used for data collection. Total enumeration technique was used to select all 1019 HND students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Moreover, according to Panmei and Waluyo (2021), the improvement in proficiency in language use among students leads to higher grades. This is supported by Sahragard, (2009), as mentioned in the study by Rafiu and Nwalo (2016), indicating that students with excellent language skills are more proficient in using language and ultimately achieve higher grades. Therefore, language proficiency and communication skills are regarded as crucial aspects in the development and establishment of cross-cultural connections (Rao, 2019).…”
Section: Introductionmentioning
confidence: 60%
“…Moreover, according to Panmei and Waluyo (2021), the improvement in proficiency in language use among students leads to higher grades. This is supported by Sahragard, (2009), as mentioned in the study by Rafiu and Nwalo (2016), indicating that students with excellent language skills are more proficient in using language and ultimately achieve higher grades. Therefore, language proficiency and communication skills are regarded as crucial aspects in the development and establishment of cross-cultural connections (Rao, 2019).…”
Section: Introductionmentioning
confidence: 60%
“…Similar to this finding, a study done in Nigeria showed that competence in the required English language was determining the students' academic performance. 16,17 It is also supported by another study done at the Be nadir University, Malaysia which found that communication skill was among the identified factors that promote academic performance. 18 It is clear that the English language is the medium of instruction for higher education trainings.…”
Section: Discussionmentioning
confidence: 79%
“…As vital as cataloguing and classification are to maximising the usage of library information resources, it has been established by Jimoh and Nwalo (2016); David-West and Angrey (2018) that most libraries have not attached importance to cataloguing and classification. This makes it difficult for library users to identify, find, locate, retrieve and eventually use library collections optimally.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…The output of cataloguing and classification is to have a catalogue and assigned call number, which will aid in finding and location of information materials on the shelves. Jimoh and Nwalo (2016) succinctly viewed cataloguing as the process of describing books and other information materials, showing the bibliographic details such as author, editor, publisher, series, tracing and other access points. It entails the process through which a library catalogue is created in order to achieve easy retrieval of information.…”
Section: Introductionmentioning
confidence: 99%